The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/brain/awy288
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal multimodal MRI as prognostic and diagnostic biomarker in presymptomatic familial frontotemporal dementia

Abstract: See Boeve and Rosen (doi:) for a scientific commentary on this article.Jiskoot et al. present evidence of presymptomatic reduction in white matter integrity and grey matter volume in familial FTD, with the largest declines in the uncinate fasciculus, genu corpus callosum, and frontotemporal, cingulate and insular cortex. Multimodal MRI parameters may be valuable prognostic biomarkers in familial FTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
98
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(122 citation statements)
references
References 81 publications
15
98
4
Order By: Relevance
“…One of the key findings in our study is the accelerated changes in mI/Cr and NAA/mI that occurred in approximately 2 years prior to symptom onset, suggesting a change in the trajectory of 1 H MRS metabolite ratios prior to symptom onset. Our findings are consistent with the trajectories reported in a recent longitudinal study of converters with MAPT and GRN mutations, demonstrating that loss of white matter integrity and grey matter volume were present 2 years before symptom onset . In addition, previous cross‐sectional studies in asymptomatic MAPT mutation carriers report presence of 1 H MRS metabolite ratio abnormalities, grey matter atrophy, loss of white matter integrity, and functional connectivity with range of 5 to 30 years before the estimated age of symptom onset.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…One of the key findings in our study is the accelerated changes in mI/Cr and NAA/mI that occurred in approximately 2 years prior to symptom onset, suggesting a change in the trajectory of 1 H MRS metabolite ratios prior to symptom onset. Our findings are consistent with the trajectories reported in a recent longitudinal study of converters with MAPT and GRN mutations, demonstrating that loss of white matter integrity and grey matter volume were present 2 years before symptom onset . In addition, previous cross‐sectional studies in asymptomatic MAPT mutation carriers report presence of 1 H MRS metabolite ratio abnormalities, grey matter atrophy, loss of white matter integrity, and functional connectivity with range of 5 to 30 years before the estimated age of symptom onset.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with the trajectories reported in a recent longitudinal study of converters with MAPT and GRN mutations, demonstrating that loss of white matter integrity and grey matter volume were present 2 years before symptom onset. 11 In addition, previous cross-sectional studies in asymptomatic MAPT mutation carriers report presence of 1 H MRS metabolite ratio abnormalities, 3 grey matter atrophy, 12 loss of white matter integrity, 13 and functional connectivity 14 with range of 5 to 30 years before the estimated age of symptom onset. It should be noted that the cross-sectional studies estimated the age of onset by the information available from the carriers of the MAPT mutation type.…”
Section: Discussionmentioning
confidence: 95%
“…Previous cross-sectional MRI studies demonstrated atrophy in the anteromedial temporal lobe and orbitofrontal cortex in asymptomatic MAPT mutation carriers (6,19,20), while others found no difference between asymptomatic MAPT mutation carriers and controls (6,7,33). Recently, two longitudinal studies from a cohort of asymptomatic MAPT mutation carriers have reported that hippocampal volumes decline during a 2-year follow-up, but no cortical atrophy was found in longitudinal analysis with 4 years of follow-up (21,22). During a 10year follow-up, the rates of temporal lobe atrophy were accelerated in asymptomatic MAPT mutation carriers who were asymptomatic during follow-up, while accelerated atrophy rates in the temporal, parietal and frontal lobes were reported in MAPT mutation carriers who became symptomatic compared to non-carriers (23).…”
Section: Mapt_smrimentioning
confidence: 98%
“…Structural magnetic resonance imaging (sMRI) has captured cortical degeneration with a mutation-specific neurodegeneration pattern years before onset of clinical symptoms in presymptomatic familial FTLD mutation carriers (6,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Studies of sMRI using different analysis methods, such as region of interest (ROI) in specific brain regions, cortical thickness analysis and voxel-based morphometry (VBM), could capture the gray matter and white matter volumes, cortical thickness, and the subcortical gray matter volume.…”
Section: Structural Mrimentioning
confidence: 99%
“…Longitudinal studies are crucial to identify genetic and environmental factors that influence the rate of these brain changes throughout development (Giedd et al, 1999;Gogtay et al, 2004;Shaw, Gogtay, & Rapoport, 2010) and aging (Raz et al, 2005). Interindividual differences in brain development are associated with general cognitive function (Ramsden et al, 2011;Schnack et al, 2015;Oschwald et al, 2019), and risk for psychiatric disorders (Shaw et al, 2009;Liberg et al, 2016) and neurological diseases (Reiter et al, 2017;Eshaghi et al, 2018;Jiskoot et al, 2019). Genetic factors involved in brain development and aging overlap with those for cognition (Brans et al, 2010;Brouwer et al, 2014) and risk for neuropsychiatric disorders (Brans et al, 2008).…”
Section: Introductionmentioning
confidence: 99%